The performance of West African Dwarf goats and sheep fed silage and silage plus concentrate - Adebowale, E.A. (1983)
The experiments reported here were specifically designed to compare in tropical sheep and goats the digestibility, energy and nitrogen utilization of silages and silage plus concentrate under identical environmental conditions. In addition, growth trials were also conducted. The first trial utilized West African dwarf rams while the other utilized bucks under the same environmental conditions. Each trial compared: Maize silage 100% (Diet A), Maize silage 75% +concentrate 25% + (Diet B), maize silage 50% + concentrate 50% (Diet C) and Maize silage 25% + concentrate 75% (Diet D). The silage and concentrate were thoroughly mixed for diets B to D before they were offered. Eight animals from each species were randomly selected and placed on each diet. Growth studies lasted four months. Goats maintained their weight on the high-moisture silages about 1.6g/days and the sheep in fact lost weight (-10.20g/day). However, increased concentrate % in diet resulted in increased liveweight gain by the sheep rising to 103.60g/day when concentrate % was as high as 75%. The picture differs for the goat. Increasing live weight gain was obtained up to the 50% concentrate level in diet, beyond this, gain fell from 68.8g/day to 59.0; although the difference was not significant (P